2011
DOI: 10.1002/gj.1314
|View full text |Cite
|
Sign up to set email alerts
|

A 3.51 Ga bimodal volcanics‐BIF‐ultramafic succession from Singhbhum Craton: implications for Palaeoarchaean geodynamic processes from the oldest greenstone succession of the Indian subcontinent

Abstract: The Palaeoarchaean greenstone belt of the southern Iron Ore Group (SIOG) (3.51 Ga) in the Singhbhum Craton, eastern India, includes lowstrained and low-greenstone grade bimodal volcanics, Banded Iron Formation (BIF) and chromiferous ultramafics as enclaves within tonalitetrondjhemite-granodiorite (TTG) granitoids, collectively referred to as the Singhbhum Granite (3.4 Ga to 3.1 Ga). The succession comprises, from base to top, a lower unit of massive and pillowed basalt conformably overlain by dacitic lava and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 85 publications
(54 citation statements)
references
References 123 publications
(237 reference statements)
1
53
0
Order By: Relevance
“…2). Based on their sedimentological analysis in combination with major, trace and REE geochemistry, these authors have inferred an oceanic suprasubduction zone geodynamic setting during the southern IOG sedimentation (Mukhopadhyay et al, 2012; see also Chaudhuri et al, 2015). Our Nd isotopic data thus corroborate the inference of a fore-arc basin setting on Singhbhum-type Mesoarchaean crust as proposed by earlier researchers.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…2). Based on their sedimentological analysis in combination with major, trace and REE geochemistry, these authors have inferred an oceanic suprasubduction zone geodynamic setting during the southern IOG sedimentation (Mukhopadhyay et al, 2012; see also Chaudhuri et al, 2015). Our Nd isotopic data thus corroborate the inference of a fore-arc basin setting on Singhbhum-type Mesoarchaean crust as proposed by earlier researchers.…”
Section: Discussionsupporting
confidence: 88%
“…Interestingly, a subduction-accretion complex in the Singhbhum during the Palaeo-Mesoarchaean time has been inferred by several authors (Saha et al, 2004;Mukhopadhyay et al, 2012; see also Prabhakar andBhattacharya, 2013, Chaudhuri et al, 2015). Based on their Sm-Nd isotope data, Saha et al (2004) have inferred that the provenance of the late Archaean Birtola sandstone (see Mazumder et al, 2012a for discussion) formed in an island arc setting.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Mafic granulite is medium-to coarse-grained and composed of clinopyroxene, garnet, quartz, plagioclase, ilmenite and hornblende Ghosh et al, 2010;Mukhopadhyay et al, 2012). Samples used in the present study are shown in the map.…”
Section: Textural and Mineralogical Evolutionmentioning
confidence: 94%
“…1a) records a remarkable Archean growth history (Saha, 1994). Its southern margin is composed of high-grade granulites along with mediumgrade metasedimentary and metavolcanic rocks, collectively termed as the Rengali Province (Crowe et al, 2001(Crowe et al, , 2003Dobmeier and Raith, 2003) that separate the PaleoeMesoarchean granitegreenstone terrane of the SC (e.g., Saha, 1994;Mukhopadhyay et al, 2012) from the essentially high-grade PaleoeMesoproterozoic Eastern Ghats Mobile Belt (EGMB) Das et al, 2011;Korhonen et al, 2011;Gupta, 2012;Dasgupta et al, 2013 and references therein). Although the Rengali Province constitutes a part of the EGMB, its rock types, metamorphic style and isotopic signatures are different from the major part of the EGMB, known as the Eastern Ghats Province or EGP (Dobmeier and Raith, 2003).…”
Section: Introductionmentioning
confidence: 99%